ANA-Negative Hydralazine-Induced Pericardial Effusion. (17th December 2017) - Zeitjian, Vicken; Mehdizadeh, Azar
Abstract : This case describes a patient with pericardial effusion as a phenomenon of the drug-induced lupus erythematosus (DILE) syndrome due to hydralazine. The relevance of this case report lies in the fact that although hydralazine has been a known causative agent of DILE, its presentation may involve a negative anti-nuclear antibody (ANA) study. Pericardial effusion is a documented adverse effect as a result of hydralazine use. It is typically common to screen for DILE with the serum ANA test prior to proceeding to more costly and specific tests (i.e., anti-histone antibody). As per our literature review, this is the second case of hydralazine causing DILE with a negative ANA. As in our case, although the screening serum ANA is the initial next best step for suspicion of DILE by hydralazine, it is important to consider the diagnosis without ANA positivity.